Titanium ions form particles that activate and execute interleukin‐1β release from lipopolysaccharide‐primed macrophages - Pettersson, M.; Kelk, P.; Belibasakis, G. N.; Bylund, D.; Molin Thorén, M.; Johansson, A. (Journal of periodontal research, 2017)
Background and Objective Peri‐implantitis is a destructive inflammatory process characterized by destruction of the implant‐supporting bone. Inflammasomes are large intracellular multiprotein complexes that play a central role in innate immunity by activating the release of proinflammatory cytokines. Although inflammasome activation has previously been linked to periodontal inflammation, there is still no information on a potential association with peri‐implantitis. The aim of this study was to examine cytotoxic and proinflammatory effects, including inflammasome activation, of metals used in dental implants, in an in vitro model, as well as from clinical tissue samples. Material and methods Human macrophages were exposed to different metals [titanium (Ti), cobalt, chromium and molybdenum] in a cell‐culture assay. Cytotoxicity was determined using the neutral red uptake assay. Cytokine secretion was quantified using an ELISA, and the expression of genes of various inflammasome components was analysed using quantitative PCR. In addition, the concentrations of interleukin‐1β (IL‐1β) and Ti in mucosal tissue samples taken in the vicinity of dental implants were determined using ELISA and inductively coupled plasma mass spectrometry, respectively. Results Ti ions in physiological solutions stimulated inflammasome activation in human macrophages and consequently IL‐1β release. This effect was further enhanced by macrophages that have been exposed to lipopolysaccharides. The proinflammatory activation caused by Ti ions disappeared after filtration (0.22 μm), which indicates an effect of particles. Ti ions alone did not stimulate transcription of the inflammasome components. The Ti levels of tissue samples obtained in the vicinity of Ti implants were sufficiently high (≥ 40 μm) to stimulate secretion of IL‐1β from human macrophages in vitro. Conclusion Ti ions form particles that act as secondary stimuli for a proinflammatory reaction.